Integrative Perinatal Management Enhanced the Advantage of Prenatal Diagnosis on Critical Pulmonary Valve Stenosis: An Observational Preliminary Study - Li, Jiawen; Li, Gang; Shi, Xiaoqing; Wang, Chuan; Duan, Hongyu; Zhou, Kaiyu; Hua, Yimin; Li, Yifei (Frontiers in Pediatrics, 2020)
Background: Percutaneous balloon valvuloplasty (PBPV) is recommended as first choice treatment for critical pulmonary stenosis (CPS). A concept of perinatal integrative management has been developed. Unfortunately, the evidence on the advantage of integrative management for CPS during perinatal period is absent. Methods: A single center observational preliminary research has been developed, and three groups have been enrolled. There were 42 children with CPS were enrolled for this study between Jan 2014 and Dec 2017 in our center, and their follow-up duration is least 1 year. There groups had been set up as integrative perinatal management group (Group I) who received prenatal diagnosis with perinatal management to maintain circulation and optimized PBPV procedure, prenatal diagnosis group (Group PR) who received a diagnosis of pulmonary stenosis before birth without any monitoring and perinatal management, and the postnatal diagnosis group (Group PO) received the CPS diagnosis after birth. Result: There were 13 patients enrolled in Group I, 11 babies enrolled in Group PR, while 18 cases were included in Group PO. The Integrative management help to put the timing of PBPV in advance. The age for PBPV in Group I was 9.38±5.58 days, while Group PR and PO were 24.54±4.87 and 49.11±9.50 days, respectively. The average peak transvalvular gradient (PGs) of perinatal management group (Group I) and prenatal diagnosis group (Group PR) remained in a stable level. However, the average PGs of Group PO was elevated in progress during follow-up, Moreover, the follow-up data from Group I revealed an advantage in keeping RV development and functional restore. There was no difference among three group in ratio of re-intervention and postoperative moderate pulmonary regurgitation during 1 year follow-up (p >0.05). Conclusion Prenatal diagnosis help to improve the outcomes of PBPV. Moreover, the perinatal integrative medical management would enhance the advantage of prenatal diagnosis. However, this research is still a small size cohort study, and the limited population number and follow-up duration were the major limitations to expend the conclusion in hint.